Analysis of teacher ability effect on student learning achievement - Cawir Refinus Purba; Benyamin Situmorang; Rosmala Dewi; Yasaratodo M.S; Yohanes Kefi; Taufiq Ramadhani; Yuni Selia (Cendikia : Media Jurnal Ilmiah Pendidikan, 2023)
This study aims to determine the effect of the teacher's ability on student achievement. The population and sample in this study is at SMP Rumah Harapan Tobasa Private Middle School amounted to 420 students. The data collection method in this study was a questionnaire or questionnaire. The data analysis technique used was simple linear regression analysis, t-test and determination test. Based on the results of data processing, it is concluded that the teacher's ability had a positive and significant effect on student achievement at Rumah Harapan Tobasa Middle School. After that the coefficient of determination of the teacher's ability on student achievement is 0.434 which means that 43.4% of the variability of student achievement can be explained by the teacher's ability variable, while the remaining 56.6% is explained by other variables not examined in this study.